Atmospheric dispersion of hydrogen sulfide using a modified ARPS model: a case study - Orcellet, Emiliana Elisabet (2022)
Exposure to disgusting smells constitutes a type of atmospheric pollution from industrial and human activities. Complaints stemming from various sources of unpleasant odors have become a serious concern in both sparsely and densely populated countries. Hydrogen sulfide is a compound characterized by its disgusting odor. In this work, a new chemical reaction was incorporated to Advanced Regional Prediction System (ARPS) model, to calculate the H2 S air concentrations. A turbulent boundary layer flow is computed using the LES code ARPS 4.5.2. A LES coupled with a Lagrangian stochastic model has been applied to the study of reactive scalar dispersion downwind of a localized source of H2 S. The study case corresponds to the H2 S emission of cellulose mill. Two bad odor event was evaluating in order to compare the result of the model with the measured concentrations. The results of this model application provides good description of the plumes for two event of bad odor records in the zone. The values resulting from the analysis of the air samples are within the concentration range estimated by the model. The model is a valid and useful tool to simulate atmospheric pollution episodes that involve non-conservative pollutants, that is, chemical species that, when in contact with the atmospheric components, react, and giving rise to the formation of secondary compounds. It is possible used the developed modeling system in cases of diagnosis and prognosis of real situations and even emergencies, with an appropriate level of precision for studies of this type.